Pengaruh Leverage, Opini Audit, APBD Terhadap Audit Delay pada Kabupaten/Kota di Indonesia Bagian Tengah - Annisa Fitriana; Diska Arliena Hafini (CV. Ulil Albab Corp, 2023)
The study aims at finding out the effect of leverage, audit opinion, local revenue, and expenditure budgets on audit delay in regencies/cities in Central Indonesia including Bali, NTB, and NTT. The study used audit reports on local government financial reports for Bali, NTB, and NTT provinces issued by the Indonesian Audit Board (BPK) for the 2020 and 2021 periods. Based on the purposive sampling method, the number of districts/cities used in the study is 41 districts/cities. The independent variables in the study are leverage, audit opinion, and regional revenue and expenditure budget (APBD), while the dependent variable is audit delay. The results of the study showed that the leverage and regional revenue and expenditure budget variables do not have a significant positive effect on audit delay, and the audit opinion variable has a significant negative effect on audit delay.